2018
DOI: 10.1590/rbz4720170303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary fat sources and conjugated fatty acid on egg quality, yolk cholesterol, and yolk fatty acid composition of laying hens

Abstract: This study was conducted to investigate the effects of dietary fats (tallow [TO] or linseed oil [LO]) or conjugated linoleic acid (CLA), singly or in combination, on laying performance, yolk lipids, and fatty acid composition of egg yolks. Three hundred 50-week-old laying hens were given one of five diets containing 2% TO; 1% TO + 1% CLA (TO/CLA); 2% LO; 1% LO + 1% CLA (LO/CLA); and 2% CLA (CLA). Laying performance, egg lipids, and serum parameters were not altered by dietary treatments. Alpha-linolenic acid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…Different fat sources did not affect the indicators of liver functions (i.e., GPT and GOT) ( Manterys et al., 2016 , Keum et al., 2018 ), which indicates that BSFL oil did not induce toxic or adverse effect on liver functions. As to serum cholesterol, perplexed results were emerged from this study.…”
Section: Discussionmentioning
confidence: 91%
“…Different fat sources did not affect the indicators of liver functions (i.e., GPT and GOT) ( Manterys et al., 2016 , Keum et al., 2018 ), which indicates that BSFL oil did not induce toxic or adverse effect on liver functions. As to serum cholesterol, perplexed results were emerged from this study.…”
Section: Discussionmentioning
confidence: 91%
“…Besides, CS contain high percentage of unsaturated fatty acids 93.44%, mainly 61.69% oleic acid, 22.12% linoleic and 6.32% linolenic acid (Farrag, 2019), these essential fatty acids of canola oil are involved in its utilization mode, taste and suitable odor, lead to increasing hen feed consumption (g/ hen/day), which in turn correlate with the significant increase in hen-day egg production (%), egg mass (g egg/hen/day) and improving the final body weight of supplemented groups. Moreover, feeding birds on diets containing unsaturated fatty acids has improved their lipid metabolism and productive performance (Keum et al, 2018). In accordance with obtaining results, (Przybylski et al, 2013;Sharafi et al, 2015) reported 7% saturated acids, including palmitic and stearic acid, and high levels of unsaturated fatty acids 93%, including 61% oleic acid, 11% linolenic acid, and 21% linoleic acid in CS, this unique composition may provide the laying quail with essential fatty acids, energy and bioactive materials during the bird's life production resulted in a positive impact on egg production and egg weight ( Sharafi et al, 2015;Ibrahim et al, 2018).…”
Section: Laying Quail Performancementioning
confidence: 99%
“…The FAs composition of the MLCFAs was: 0.50% caproic acid (C6:0), 4% caprylic acid (C8:0), 4% capric acid (C10:0), 44% lauric acid (C12:0), 20% myristic acid (C14:0), 10% palmitic acid (C16:0), 0.25% palmitoleic acid (C16:1), 4% stearic acid (C18:0), 10% oleic acid (C18:1), 3% linoleic acid (C18:2) and 0.25% linolenic acid (C18:3). FAs were analysed as described by Keum et al (2018).…”
Section: Experimental Designmentioning
confidence: 99%